A measurement of the K-S lifetime - Lai, A; Marras, D; Batley, JR; Bevan, A; Dosanjh, R; Gershon, T; Hay, B; Kalmus, G; Lazzeroni, C; Munday, D; Needham, MD; Olaiya, E; et al. (2002)
The lifetime of the lowest-mass charm bryon is measured to provide a window for the nonperturbative sector of heavy quark decay. The data are obtained in a colliding beam environment in the CLEO II.V detector at the Cornell Electron Storage Ring. In this environment, the event topologies and backgrounds are very different from those encountered in high energy fixed-target experiments.